MEASUREMENT HAND WASHING COMPLIANCE FIVE MOMENT BY NURSE AT CIJANTUNG KESDAM HOSPITAL - Lea merimta Tarigan; Aisyah Safitri (STIKes Kepanjen, 2020)
Healthcare Associated Infection (HAIs) are infections that occur during the treatment process in a hospital or in other health care facilities, where the patient is not infected or not during the incubation period, or hospital-acquired infections appear after discharge, as well as infections in health workers who occur because of their work. The purpose of this study was to find out the direct and indirect effects and the magnitude between supervision, availability of infrastructure, PPI training, compensation, work commitment and perception of compliance with five-time hand washing by nurses at the Cijantung Hospital. The method used in this study is a quantitative approach that uses cross-sectional design. The sample used was 80 nurses as respondents. The analytical method used is the Structural Equation Model (SEM) using SmartPLS 2.0 and SPSS 20. The results of hypothesis testing with the Structural Equation Model (SEM) with the smartPLS method found that the influence of supervision variables (26.8%), availability of infrastructure (11, 12%), PPI training (7.03%), compensation (21.36%), work commitment (8.86%) and perceptions (6.2%) of compliance with five-time hand washing by nurses at the Kesdam Jaya Cijantung Hospital. It would be better for the hospital to continue making improvements by increasing awareness of the importance of the implementation of hand washing to prevent the occurrence of nosocomial infections, and supervise the implementation of hand washing.